Student-centred learning in a passive learning environment: students' perception and performance - Abdul Hamid, Fatima; Nik Nazli, Nik Ahmad (Faculty of Economics and Management, Universiti Putra Malaysia, 2013)
This study attempts to seek students’ preference of teaching methods for the Accounting Theory course and to compare students’ performance in classes using student-centred learning (SCL) with traditional lecture method (TLM), in a passive learning environment. Results reveal that the teaching method most frequently ranked highest by students is still the TLM. Also, there is no significant difference between students’ performance under SCL or TLM. While this is unexpected, it is possible that SCL may not have the expected positive results when the students have been largely exposed to a passive learning environment. The results have important implications for accounting educators and policy-makers in Malaysia and other countries, particularly in the Asia-Pacific region where the learning environment is more passive.